Customer Experience Management - the Mantra for Success - Raju, J K; Walavalkar, Deepali (Ushus Journal of Business Management, 2006)
The past decade has seen several changes in the business environment and markets are flooded with several me-too brands making the consumer perplexed and further increasing his search time. With new brands encroaching the mind space of the customers and displacing the existing ones, the only differentiator the brands can rely on for lasting advantage is the experience that lingers in the customer's head. Providing a meaningful experience is a challenging task for companies and they need to incorporate a CEM (customer experience management) culture by managing their customer, brand and their operational processes. CEM would not be possible without managing employee experience because they act as an interface between the company and the customer. It is also important to gain insights regarding perceptions of customers through research, so that changes can be incorporated to improve experiences in the future. In order to achieve strategic advantage organisations need to adopt policies and strategies that promote and enhance the experience environment.